MASALAH TESTIMONIUM DE AUDITU SEBAGAI ALAT BUKTI DALAM PERKARA PERDATA - Juhaipah Juhaipah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTResearch singer in order for the review to know the strength of the laws of evidence witness testimonials de auditu hearts civil, hearts HAL proof Of Testimony For courts especially hearts civil matters set hearts Article 165 RBg / 139 HIR Up to 179 RBg / 152 HIR ABOUT Witness Examination And Article 306 RBg / 169 Up to 309 RBg / 172 HIR The testimony ON 1895 WITH Until 1902 article article 1912 of the Civil Code. In proving the parties The litigant must convince the judges ABOUT arguments Yang in Convey BECAUSE hearts verification system, hearts BECAUSE NOT equal civil law Events Events pidana.Dalam law hearts of Justice civil Truth Yang in the search and DI embodied by the judge is only formal truth.Implementation Regarding testimonials de auditu used as a tool Evidence hearts civil matters Many raises the pros and cons Among legal practitioners, ON generally Testimony testimonials de auditu NOT be used as a tool of direct evidence but as a proof of conjecture WITH consideration of objective and rational And allegation ITU can be in the Make Something Elementary proof. Testimuniom de auditu acceptance as a means of evidence hearts yurisprodensi By THEREFORE Yurisprodensi as prayer One legal source Very Important official existence when linked WITH telecoms judge Yang NOT Only Just implement the law but Also Need to dig to find a legal review, OR BY creates law.